Analysis of Music Art Learning on Material Recognizing the Shape and Sound of Musical Instruments in Elementary Schools - Lestari, Dinda Rizki; Respati, Resa; Setiadi, Pidi Mohamad (Attadib: Journal of Elementary Education, 2024)
Analysis of music art learning on material recognizing the shape and sound of musical instruments in elementary schools aims to find out how the implementation of learning recognizes the shape and distinguishes the sound of musical instruments in elementary schools. The research method used is qualitative descriptive. Data collection techniques use interviews, observation, and documentation. Data analysis through data reduction, data presentation and conclusion. From the results of the analysis, it was obtained that learning to recognize the shape and sound of musical instruments in elementary schools was seen from the following 7 things, namely: 1) There are two attitudes shown by students, namely a positive attitude and a negative attitude; 2) The teacher does not have the ability to play a musical instrument; 3) Learning planning is carried out by preparing a learning implementation plan (RPP); 4) The learning methods used vary and can motivate students; 5) Teaching materials used in the form of student books, student handbooks, and LKS; 6) The learning media used is still sober and not in accordance with the objectives and learning materials; and 7) Learning evaluation only measures aspects of knowledge, without measuring aspects of attitudes and skills.